Model development and GUI of renewable energy systems considering battery degradation - Toh, Hubert Ze En (Nanyang Technological University, 2023)
As society advances technologically, demand for electricity generation is rising equally quickly. This is compounded with other issues arising from the use of fossil fuels to produce electricity, such as pollution and limited resources. Naturally, renewable energy sources are garnering more interest as they solve the immediate problems presented by fossil fuels.